2016
DOI: 10.1016/j.jmmm.2015.10.012
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic properties of sulfur-doped graphene

Abstract: While studying magnetism of d-and f-electron systems has been consistently an active research area in physics, chemistry, and biology, there is an increasing interest in the novel magnetism of p-electron systems, especially in graphene and graphene-derived nanostructures. Bulk graphite is diamagnetic in nature, however, graphene is known to exhibit either a paramagnetic response or weak ferromagnetic ordering. Although many groups have attributed this magnetism in graphene to defects or unintentional magnetic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 41 publications
0
14
0
Order By: Relevance
“…242 However, in a separate study, quenching of the previously developed local magnetic moment induced by vacancies was observed via S substitutional doping of graphene, which led to diamagnetic, weak ferromagnetic and antiferromagnetic states in graphene. 243 The S-G system maintains good electrocatalytic activity for the oxygen reduction reaction. 235 S-G prepared via acid exposure of graphene has been proven to be an excellent solid catalyst.…”
Section: Substitution Of Group Via Elements In Graphenementioning
confidence: 99%
“…242 However, in a separate study, quenching of the previously developed local magnetic moment induced by vacancies was observed via S substitutional doping of graphene, which led to diamagnetic, weak ferromagnetic and antiferromagnetic states in graphene. 243 The S-G system maintains good electrocatalytic activity for the oxygen reduction reaction. 235 S-G prepared via acid exposure of graphene has been proven to be an excellent solid catalyst.…”
Section: Substitution Of Group Via Elements In Graphenementioning
confidence: 99%
“…Based on the theoretical analysis presented below, it is speculated that upon further increase of sulfur concentration in the graphene lattice (up to ≈6.25 at%), the value of the saturation magnetization could further increase closely approaching ≈8 emu g −1 , a value reported for vertical graphenes, which are currently viewed as the magnetically strongest carbon‐based systems . Here, it should be stressed that indeed, sulfur atoms are embodied into the graphene lattice as a rise in the magnetization values is observed upon increase of sulfur doping; if sulfur atoms were simply added to the graphene sheets (i.e., as adatoms), they would saturate the dangling bonds and, hence, quench the magnetic moments induced by defects, resulting in a decrease in magnetization with potential alternation of the type of the magnetic state (from the ferromagnetic to paramagnetic or diamagnetic regime) . Such a manifestation is in line with theoretical predictions as discussed below.…”
mentioning
confidence: 91%
“…Recently, it was experimentally shown that introduction of nitrogen in the graphene lattice decreases the magnetization values compared to those of defected graphene . Identical fashion in magnetization behavior was lately observed upon doping of graphene lattice with sulfur; weakening of the magnetic response and change in the type of magnetic ordering were explained in terms of saturation of dangling bonds by sulfur atoms and, hence, quenching of local magnetic moments induced by defects existing already in undoped graphenes …”
mentioning
confidence: 99%
“…Also it was predicted that sulfur doping could open an energy band gap in graphene [8,9]. On the other hand, Zhu and coworkers [12] found that sulfur dopants quench magnetic ordering in graphene and in general sulfur changed the magnetic behavior of their samples. Other experimental studies in graphite-sulfur composites have found superconducting behavior below 35K [13].…”
Section: Introductionmentioning
confidence: 99%